Response of tow varieties of okra (Abelmoschus esculentus L. Moench) to application methods of humic acid, zolfast and their effects on qualitative charectristics of fruits - A. A., Yaseen; N. S. A., M. Al-Mousawy (Al-Qadisiyah Journal of Pure Science, 2018)
The experiment was conducted in Agriculture College, University of AL–Qadisiya from 10/4/2011 till 15/10/2011. The aim of the study was studying response of two okra cultivars (Al– Husenawyia and Al–Pteira), humic acid and zolfast application methods (foliar and addition to irrigation water) and this concentration (recommended and doubled) on qualitative charectristics of fruits The humic acid and zolfast formulas were added twice by the use of hand sprayer. The recommended concentration for humic acid and zolfast as foliar spraying were 1 ml.L-1 and 2 ml.L-1 if doubled respectively while when used with irrigation water 4.8 ml.L-1 and 9.6 ml.L-1 at double for humic acid 7.2 and 14.4 ml.L-1 for zolfast if doubled. The design of the experiment was Randomized Complete Blocks in a factorial arrangement (2×2×5) in three replications. The RLSD at 0.05 was used as a method of mean separation treatment effect was evident.The results showed: 1- Al–Husenawyia cultivar was superior on Al–Pteira cultivar in mucilage, percentage of protein, carbohydrates and oil refractive index. 2- Foliar application method of humic acid and zolfast showed beneficial effect on all parameters studies. 3- Percentage of fiber was lower with the use of zolfast compared to humic acid and control. No significant difference was found between the recommended concentrations of humic acid or zolfast in carbohydrates%, mucilage and oil refractive index. 4- The interaction between cultivars and humic acid and zolfast concentrations revealed that both cultivars had different response to the applied concentrations of humic and zolfast. Al– Husenawyia had higher percentage of fiber, mucilage, oil refractive index with the double recommended humic acid. 5- The three way interaction factors studied in the experiment revealed an increase in growth parameter of both cultivars when humic acid and zolfast were added in their higher concentration (double recommended) by foliar application. Al–Husenawyia cultivar was higher in all parameters with the use of higher concentration of humic acid and zolfast when applied with irrigation water or foliar application. The three way interaction revealed no significant difference in the percentage of oil.